Peran Pendidikan Islam dalam Membentuk Karakter, Multikultural dan Sosial yang Harmonis - Nurlita Ekasari; Rahmi Alya; Herlini Puspika Sari (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to examine the role of Islamic education in shaping multicultural character and social harmony in a diverse society. The background of the research is based on current social realities that show a decline in values such as tolerance, politeness, and social awareness, especially among youth. This research employs a qualitative method using a literature review approach, analyzing various scholarly sources and relevant journal articles. The findings indicate that Islamic education has a significant potential in developing individuals with tolerant attitudes, appreciation for diversity, and the ability to coexist peacefully. Core values such as ukhuwah (brotherhood), justice, humanity, and wasathiyyah (moderation) serve as the foundation in nurturing multicultural character. The implications suggest the importance of integrating multicultural Islamic education into the curriculum and the need for support from the government and educational institutions to build an inclusive, peaceful, and harmonious society.